Exploring the influence of haptic and olfactory cues of a virtual donut on satiation and eating behavior - Li, Benjamin Junting (2018)
Olfactory research in immersive virtual environments (IVEs) have often examined the addition of scent as part of the environment or atmosphere that act as experimental stimuli. There appears to be a lack of research on the influence of virtual foods in IVEs on human satiation. Studies based on situational cues or self-perception theory provide support for the hypothesis that touching and smelling a virtual food item may lead to increased consumption as a result of modeling expected behavior. On the other hand, studies grounded in embodied cognition suggest that satiation may take place as a result of mental simulation that resembles actual consumption behavior. In this preliminary study, we sought to explore the effects of haptic and olfactory cues through virtual food on human satiation and eating behavior. In our study, 101 participants took part in a 2 (touch: present vs absent) × 2 (scent: present vs absent) experiment where they interacted with a donut in an IVE. Findings showed that participants in the touch and scent present conditions ate significantly fewer donuts than those who were not exposed to these cues, and reported higher satiation as compared to their counterparts. However, findings were less clear with respect to participants who received both haptic and olfactory cues. As a whole, results provide preliminary support for satiation effects as a result of sensory simulation.